Behind the shield [videorecording (DVD)] : the power & politics of the NFL - Earp, Jeremy; Zirin, Dave; Marracino, Daniel (Media Education Foundation, 2022)
"In Behind the Shield, celebrated author and Nation magazine sports editor Dave Zirin tackles the myth that the NFL was somehow free of politics before Colin Kaepernick and other Black NFL players took a knee. Digging deep into the history of the league, and navigating a stunning excavation of decades of archival footage and news media, Zirin traces how the NFL, under the guise of "sticking to sports," has promoted wars, militarism, and nationalism; glorified reactionary ideas about manhood and gender roles; normalized systemic racism, corporate greed, and crony capitalism; and helped vilify challenges to the dominant order as "unpatriotic" and inappropriately "political." The result is a case study not only in the power of big-time sports to disseminate stealth propaganda and reinforce an increasingly authoritarian status quo, but also the power of activist athletes to challenge this unjust status quo and model a different, more democratic vision of America."--Provided by publisher.